2017
DOI: 10.2214/ajr.16.16130
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Aspiration Sclerotherapy of Simple Hepatic Cysts: A Systematic Review

Abstract: We found excellent results with respect to long-term efficacy and safety after aspiration sclerotherapy of hepatic cysts. Nevertheless, because of the high risk of bias in the included studies, definite conclusions regarding efficacy cannot be drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 30 publications
1
80
0
1
Order By: Relevance
“…More invasive treatments include aspiration sclerotherapy (AS), liver cyst fenestration, hepatic resection, and LT. AS involves percutaneous cyst fluid aspiration with injection of a sclerosing agent to destroy the epithelial lining and prevent future fluid secretion. AS is a safe and efficacious technique for patients who have one or a few large, dominant cysts with diameters greater than 5 cm . The majority of patients report an improvement (72%‐100%) and complete resolution of symptoms (56%‐100%).…”
Section: Initiate Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…More invasive treatments include aspiration sclerotherapy (AS), liver cyst fenestration, hepatic resection, and LT. AS involves percutaneous cyst fluid aspiration with injection of a sclerosing agent to destroy the epithelial lining and prevent future fluid secretion. AS is a safe and efficacious technique for patients who have one or a few large, dominant cysts with diameters greater than 5 cm . The majority of patients report an improvement (72%‐100%) and complete resolution of symptoms (56%‐100%).…”
Section: Initiate Treatmentmentioning
confidence: 99%
“…The majority of patients report an improvement (72%‐100%) and complete resolution of symptoms (56%‐100%). Cyst volume reduction ranges from 76% to 100% . A common complication is postprocedural pain from peritoneal irritation.…”
Section: Initiate Treatmentmentioning
confidence: 99%
“…Next, a sclerosing agent (eg ethanol, tetracycline, polidocanol) is injected, which damages the inner epithelial lining resulting in regression of the cyst . A recent systematic review found that aspiration sclerotherapy reduces proportional cyst volume by 76%‐100% . Aspiration sclerotherapy comes with complications such as pain, ethanol intoxication, cyst bleeding and rarely cyst infections .…”
Section: Management Of Portal Hypertension In Pldmentioning
confidence: 99%
“…Other clinical manifestations may include epigastric fullness nausea, breathlessness, infection and intracystic haemorrhage and in more rare cases cardiac compromise . A wide range of interventions is available for the treatment of symptomatic or complicated cysts; these include simple aspiration, liver resection, and transplantation for incapacitating PCLD . Intraperitoneal fenestration by deroofing, the excision of the cyst dome to allow the free drainage of the cystic epithelium into the peritoneal cavity is the most widely used procedure.…”
Section: Introductionmentioning
confidence: 99%